Scientific Research Conception Guided by General Practice Thinking - YU Dehua (Zhongguo quanke yixue, 2023)
With the increasing attention to primary care services and the growing of society needs, a large number of scientific research questions have emerged in the field of general practice and community health. This problem-based scientific research promotes the construction and development of the discipline. The discipline connotation characteristics and professional thinking elements of general practice belonging to the scope of clinical medicine and community health focusing on public health determine the design focus and research methods of scientific research. However, the common problem of scientific research in general practice and community health in China is the lack of attention to the characteristics of scientific general practice research thinking and insufficient depth of thinking. This paper explains the implemention of scientific research in detail guided by general practice thinking in three aspects including the identification and location of research questions, the building of multidisciplinary research team to achieve technology crossover and the development of holistic and systematic research design based on the elements of general practice thinking ("human-centred", holistic approach, systematization), supplemented by the practice cases of the department of general practice of Yangpu Hospital, Tongji University, in order to provide a reference for researchers on general practice and community health to implement scientific research focus on the connotation characteristics, and contribute to the positive development of scientific research in general practice.